Genetic Architecture of Human Obesity Traits in the Rhesus Macaque. Issue 3 (11th February 2019) - Raboin, Michael J.; Letaw, John; Mitchell, Asia D.; Toffey, David; McKelvey, Jessica; Roberts, Charles T.; Curran, Joanne E.; Vinson, Amanda
Abstract : Objective: Whereas the metabolic consequences of obesity have been studied extensively in the rhesus macaque, corollary genetic studies of obesity are nonexistent. This study assessed genetic contributions to spontaneous adiposity in this species. Methods: Phenotypic variation by age class and sex for BMI, waist to height ratio, waist to thigh ratio, and waist circumference was assessed in 583 macaques. Total and sex‐specific heritability for all traits was estimated, including waist to thigh ratio adjusted for BMI, as well as genotypic and phenotypic correlations. In addition, functional genetic variation at BDNF, FTO, LEP, LEPR, MC4R, PCSK1, POMC, and SIM1 was assessed in four animals with extreme spontaneous adiposity. Results: Trait heritability in the combined sample was low to moderate (0.14‐0.32), whereas sex‐specific heritability was more substantial (0.20‐0.67). Heritability was greater in females for all traits except BMI. All traits were robustly correlated, with genetic correlations of 0.63 to 0.93 indicating substantial pleiotropy. Likely functional variants were discovered in the four macaques at all eight human obesity genes, including six missense mutations in BDNF, FTO, LEP, LEPR, and PCSK1 and, notably, one nonsense mutation in LEPR . Conclusions: A moderate polygenic contribution to adiposity in rhesus macaques was found, as well as mutations with potentially larger effects in multiple genes that influence obesity in humans.